Energy-dense, nutrient-poor food and beverage sales in Australia: where and when products are sold, and how sales are changing over time. Issue 2 (12th February 2021) - Gearon, Emma; Riesenberg, Devorah; Backholer, Kathryn; Cameron, Adrian J; Sacks, Gary; Ni Mhurchu, Cliona; Peeters, Anna
Abstract: Objective: To quantify sales trends for key energy-dense, nutrient-poor (EDNP) foods and beverages over 5 years in Australia. Design: The Euromonitor Global Market Information Database and linear regression models were used to estimate average annual change in sales per capita of thirteen EDNP food categories and two EDNP beverage categories (defined using Australian Dietary Guidelines) over 5 years (2012–2017 for foods and 2011–2016 for beverages). The average annual change in sales was divided by the observed sales in 2012 (foods) or 2011 (beverages) to estimate the average percentage-change in sales per capita per annum. Setting: All major retail outlets in Australia. Participants: Euromonitor Global Market Information Database sales data. Results: Between 2012 and 2017, sales per capita per annum of frozen pizza (6 %), pastries (5 %), potato chips (crisps) (5 %), tortilla chips (3 %), chocolate confectionery (2 %), frozen processed potatoes (2 %), ice cream (2 %) and sugar confectionery (0·2 %) increased. There were no changes in sales of sweet biscuits, chocolate spreads and cakes, and sales of savoury biscuits and processed meat decreased (–2 and –1 %, respectively). Between 2011 and 2016, sales per capita per annum of sports and energy drinks increased (4 %), sales of regular (sugar-sweetened) cola (–6 %) and all non-cola soft drinks (–1 %) decreased and sales of diet cola did not change. Conclusions: Sales of EDNP foods and beverages generally increased or remained stable relative to population growth. Our results demonstrate the need for public health policies to reduce sales of EDNP foods and beverages.